Timing of intravenous prophylactic antibiotics for preventing postpartum infectious morbidity in women undergoing cesarean delivery - حسن سحر; الدالي عصام; إدريس يحيى (Latakia University Journal -Medical Sciences Series, 2021)
Introduction: Bacterial infections during childbirth and the puerperium are among the important causes of maternal mor tality worldwide, accounting for about a tenth of the global burden of maternal mortality. While the number of deaths from this infection has decreased significantly in developed countries, the situation has not improved in resource-limited countries. With the indiscriminate use of antibiotics also, resistant strains of high virulence and high costs of treatment, morbidity and mortality began to increase. Goal: Determining the optimal timing of the intravenous infusion of a prophylactic antibiotic (ceftriaxone 2g) who 2015 in elective caesareans to reduce maternal sepsis and maternal mortality. Materials and methods: A prospective, randomized, single-blind study (RANDOMIZED Clinical TRIAL) RCT was conducted. The target population was 100 patients who will undergo elective caesarean section at Tishreen University Hospital affiliated with Tishreen University in Lattakia between 2020 and 2021. The sample will be divided randomly and equally into two groups, the first to receive intravenous antibiotics 60 minutes before cesarean section and the second during the cesarean section after clamping the umbilical cord, and the study will not go into the effects on the newborn. Results: For incisional sepsis and puerperal endometriosis, the results were in the group that received antibiotics before caesarean section (2%) and in the group that received antibiotics after umbilical cord clamping (8%), and the p value = 0.01, which is an important indicator and statistical significance in reducing the rate of sepsis. While no cases of respiratory sepsis were recorded in the two groups, p value = 0.5 and had no statistical significance. The percentage of refractory morbidity and urinary sepsis (2%) were equal in the two groups and the p value = 0.5, ie without significant or clinical statistical significance. For general sepsis, the percentage of sepsis was In the first group that received R before caesarean section (8%), while in the second group (20%) and pvalue = 2.49, we did not find a significant statistical significance. Conclusion: The use of prophylactic antibiotic before cesarean section reduced the rate of wound sepsis and puerperal endometriosis than its use during cesarean section with significant statistical and clinical value. While there was no statistically significant difference for urinary or respiratory infection or heat morbidity or for general sepsis.